(untitled) - Rao, Singiresu S. (Boston, MA, 2011)
Finite Element Analysis is an analytical engineering tool originated by the aerospace and nuclear power industries to find usable, approximate solutions to problems with many complex variables. It is an extension of derivative and integral calculus, and uses very large matrix arrays and mesh diagrams to calculate stress points, movement of loads and forces, and other basic physical behaviors. Rao provides a thorough grounding of the mathematical principles for setting up finite element solutions in civil, mechanical, and aerospace engineering applications. The new edition includes examples using modern computer tools such as Matlab, Ansys, Nastran, and Abaqus. Professional engineers will benefit from the introduction to the many useful applications of finite element analysis, and will gain a better understanding of its limitations and special uses.
Keywords: Phương pháp phần tử hữu hạn,Finite element method